PENGARUH ALIRAN TERHADAP FORMASI BED LOAD DI SUNGAI CIKAPUNDUNG-BANDUNG - Samitra, Azwar (2013)
Cikapundung is a river located in the city of Bandung. Cikapundung streams can be categorized types of turbulent flow. River transport cikapundung many carrying sediment at the time of the flood. One of the sediment transport is bed load. Bed load Material contained on the Cikapundung quite varied in size and form. Grain size found in the Cikapundung determine the kind of material available at the Cikapundung. Size varying the can be seen from flow discharge. Flow discharge that determinestype of freight carried by the flow of material. The greater the discharge flow will be the larger grain size also can be transported. Grain size that settles on the bottom of the river called the bed load. Flow discharge has important role in the process of bed load. Regime of bed load movement itself is rolling, wheels, ripples, dunes, antidunes, standing waves, jump, chute and pool. Bed load Cikapundungriver is very influential on the flow. Cikapundung river flow speed belongs to the Sub critical flow velocities. Bed load in the Cikapundung also influenced by the roughness on riverbed. Riverbed coarse can influenced the flow velocity. Roughness is also caused by bed load discharge at the bottom of river. If the river had roughness values greater then the velocity flow will be smaller. Flow velocity also has a relationship with roughness, while of the roughness has influence towards bed load which occurs at the base of the river. The greater the flow rate that happens, then the greater the bed load transported by the flow. Bed load material types contained in the flow Cikapundung is sand and very coarse sand. Keyword : Flow, Cikapundung, Sediment